Analysis of student preparedness behaviour in facing lava rainfall disasters - Hadiyati Nur Hafida Siti; Dila Putri Yuliani Ayu; Dahniar Vina; Mulia Iqlimah Aghnia; Regita Sukamto Rachma; Musiyam Muhammad; Nasurullah (E3S Web of Conferences)
Students are vulnerable to natural disasters. This is further exacerbated by the large number of schools located in disaster-prone areas, so student preparedness behaviour needs to be continuously improved. This study aims to determine the level of preparedness, awareness, action, and effect students have in dealing with the volcanic eruption of Mount Merapi. This study used quantitative research; the instrument used was a questionnaire made by taking samples at SMK Muhammadiyah 1 Salam. The sampling method was stratified random sampling from students in grades 10, 11, and 12. The assessment of students’ preparedness behaviour in dealing with rain lava was based on four variables: preparedness, awareness, action, and affect. Then, each variable was analyzed using descriptive statistics and multiple correlation analysis. The study results show that the relationship between preparedness, awareness, action, and affect shows a strong level of closeness with a value of 0.680. The study identifies critical gaps in knowledge and behavioural responses that must be addressed to enhance overall preparedness behaviour. The results underscore the importance of targeted educational interventions and community engagement in fostering a culture of resilience among students in disaster-prone areas.